2020
DOI: 10.21203/rs.3.rs-40580/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Group or individual Lifestyle-integrated Functional Exercise (LiFE)? A qualitative analysis of acceptability

Abstract: Background: The Lifestyle-integrated Functional Exercise (LiFE) program is an effective but resource-intensive fall prevention program delivered one-to-one in participants’ homes. A recently developed group-based LiFE (gLiFE) could enhance large-scale implementability and decrease resource intensity. The aim of this qualitative focus group study is to compare participants’ experiences regarding acceptability of gLiFE vs LiFE.Methods: Programs were delivered in seven group sessions (gLiFE) or seven individual h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
1
7
1
Order By: Relevance
“…Other factors that can be hypothesized to determine WTP could be the individually perceived relevance (e.g. individually perceived risk of falling) and perceived effectiveness of the intervention, the presence of other health conditions whose treatment may be given a higher priority, or the relationship with the trainer [14]. It is also not clear whether participants factored the cost of providing the intervention, and thus the additional effort required for home visits in LiFE, into their willingness to pay, which may explain the difference in WTP between program versions [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other factors that can be hypothesized to determine WTP could be the individually perceived relevance (e.g. individually perceived risk of falling) and perceived effectiveness of the intervention, the presence of other health conditions whose treatment may be given a higher priority, or the relationship with the trainer [14]. It is also not clear whether participants factored the cost of providing the intervention, and thus the additional effort required for home visits in LiFE, into their willingness to pay, which may explain the difference in WTP between program versions [20].…”
Section: Discussionmentioning
confidence: 99%
“…Those people, based on individual preferences, may still opt for the individual program despite being more costly. For example, some people may prefer individual supervision and learning the program in their own home where the activities could be adapted to the individual conditions and are therefore more easy to integrate into everyday life, whereas for others the social aspects of a group program (e.g., motivation through peer support) may be more important [13,14]. Moreover, the individual approach in LiFE could be more suitable for people for whom participation in group programs would be difficult, for example, because of physical and transport limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed positive group experiences and participants implemented 75% of the activities learned during gLiFE sessions, which is comparable to the adherence rate reported for LiFE (76%). Reicherzer et al (2021) conducted a qualitative focus group analysis that showed a high acceptance rate of gLiFE among 30 participants. gLiFE participants' attitude and motivation to participate was positively associated with learning in a group.…”
Section: Not Describedmentioning
confidence: 99%